2011
DOI: 10.1021/cn200098p
|View full text |Cite
|
Sign up to set email alerts
|

Piperidine Acetic Acid Based γ-Secretase Modulators Directly Bind to Presenilin-1

Abstract: Aβ42 is believed to play a causative role in Alzheimer’s disease (AD) pathogenesis. γ-Secretase modulators (GSMs) are actively being pursued as potential AD therapeutics because they selectively alter the cleavage site of the amyloid precursor protein (APP) to reduce the formation of Aβ42. However, the binding partner of acid based GSMs was unresolved until now. We have developed clickable photoaffinity probes based on piperidine acetic acid GSM-1 and identified PS1 as the target within the γ-secretase complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
92
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(95 citation statements)
references
References 41 publications
3
92
0
Order By: Relevance
“…S7b). GSMs have also been shown to target PS1-NTF 9,22,29 , supporting the hypothesis that these compounds could bind at the interface between APP-C99 and the substrate-docking site of g-secretase. Moreover, the region between g-and e-sites on APP-CTF has been proposed to be a binding domain for PS1-NTF 30 , and peptides mimicking this domain can selectively block Ab production, sparing Notch processing 31 .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…S7b). GSMs have also been shown to target PS1-NTF 9,22,29 , supporting the hypothesis that these compounds could bind at the interface between APP-C99 and the substrate-docking site of g-secretase. Moreover, the region between g-and e-sites on APP-CTF has been proposed to be a binding domain for PS1-NTF 30 , and peptides mimicking this domain can selectively block Ab production, sparing Notch processing 31 .…”
Section: Discussionmentioning
confidence: 57%
“…A subset of non-steroidal antiinflammatory drugs (NSAIDs) were the first Notch-sparing small molecules shown to selectively lower Ab42 and subsequently raise Ab38 both in vitro and in vivo 19,20 . These g-secretase modulators (GSMs) were initially shown to bind to APP, although some more recent studies demonstrated that they also can target g-secretase 21,22 . Although the precise molecular mechanism of action remains poorly understood, a number of these molecules have advanced to clinical trials 23 .…”
mentioning
confidence: 99%
“…E2012 (US2006/0004013), GSM-1 (WO2006/043064), GSM-5 (27), BMS-708,163 (30), L-685,458 (L458), L-682,679 (L679) (31), and L458-BPyne (32) were prepared according to published methods. The helical peptide inhibitor that targets the substrate docking site (pep11, Boc-…”
Section: Methodsmentioning
confidence: 99%
“…anistically modulate the genesis of A␤ peptides, we generated novel GSM-based photoaffinity probes (27). Here, we describe the design and synthesis of a clickable photoprobe based on the imidazole GSM E2012 (Fig.…”
Section: Design Of Potent Clickable Photoaffinity Probe Based On E201mentioning
confidence: 99%
See 1 more Smart Citation